1990
DOI: 10.1007/bf00199575
|View full text |Cite
|
Sign up to set email alerts
|

On ringing limits of the auditory periphery

Abstract: In classical hearing theory frequency and time have been treated as nearly independent acoustical dimensions. In this paper the interaction between temporal and spectral aspects is studied. An important determinant in this respect is the filtering of auditory stimuli in the cochlea. A view of auditory filtering that is balanced in frequency and time is obtained from the 'reverse-correlation function', abbreviated: revcor function. This function is derived from the response of an auditory-nerve fibre to a white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…We surmise that the system properties that make such predictions possible are the same that severely restrict the prominence of basilar-membrane harmonic distortion and other nonlinearities, especially when stimulation is confined to a single spectral level (e.g., Evans, 1989;de Boer and Kruidenier, 1990;Zwislocki et al, 1997). (1) The magnitude-and phase-frequency spectra of responses to a given type of stimulus (click or tone) presented at any one level accurately predicts responses to the other type of stimulus only at a single, specific level.…”
Section: E Nonlinear Phase Shifts In Responses To Clicks and Their Rmentioning
confidence: 93%
“…We surmise that the system properties that make such predictions possible are the same that severely restrict the prominence of basilar-membrane harmonic distortion and other nonlinearities, especially when stimulation is confined to a single spectral level (e.g., Evans, 1989;de Boer and Kruidenier, 1990;Zwislocki et al, 1997). (1) The magnitude-and phase-frequency spectra of responses to a given type of stimulus (click or tone) presented at any one level accurately predicts responses to the other type of stimulus only at a single, specific level.…”
Section: E Nonlinear Phase Shifts In Responses To Clicks and Their Rmentioning
confidence: 93%
“…To investigate the possible role of within-channel effects in CDD, we simulated the output of an auditory filter centered at the target frequency, using a gammatone filter with an equivalent rectangular bandwidth of 230 Hz (Moore et al, 1989;Patterson and Cutler, 1989;de Boer and Kruidenier, 1990). We started by generating samples of noise in the same way as described above (under methods, experiment 1).…”
Section: Within-channel Effects In Cddmentioning
confidence: 99%
“…Simple second-order resonators – harmonic oscillators – do have limitations [119], [120] and at some stage it will be necessary to consider higher order systems with dispersion and nonlinearities, particularly for DPOAEs [12], [40]. However, it is possible to show that every nonlinear model can be given a linear equivalent [132], and it is in many ways remarkable that parallel-based models can give results fairly similar to serial-based equivalents.…”
Section: Resultsmentioning
confidence: 99%
“…In earlier work by this author [119], [120], revcor functions were fitted to cochlear nerve data and it was found that the delays, after accounting for synaptic delays, were measurable in microseconds. As an elaboration, the 1989 paper also measured the order of the equivalent filters and found that the order required was at least 2 (that of a simple mass–spring system) but sometimes higher (4 or even 10 at high frequencies), meaning that at the level of the nerve a simple resonator is an oversimplification and a higher-order filter may be necessary.…”
Section: Discussionmentioning
confidence: 99%